2021
DOI: 10.1186/s12883-021-02392-5
|View full text |Cite
|
Sign up to set email alerts
|

Translation, adaptation and validation of the Bulgarian version of the King’s Parkinson’s Disease Pain Scale

Abstract: Background The purpose of the present study was to translate and cross-culturally adapt the King’s Parkinson’s Disease Pain Scale (KPPS) into Bulgarian and to investigate its psychometric properties in order to provide a validated Parkinson’s disease-specific pain instrument in Bulgarian language (KPPS-BG). Methods Translation into Bulgarian and a cultural adaptation were performed to obtain KPPS-BG. A total of 162 patients with idiopathic Parkinso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
4
7
1
Order By: Relevance
“… 4 , 8 , 9 , 22–25 The mean total KPPS score in our study was 41.2±26.8, which was higher than the results of some previous studies. 14 , 15 , 22 According to the Ford classification, the most common types of PD-related pain are musculoskeletal pain and dystonia-related pain, followed by neuropathic radicular pain and central pain, which is consistent with the results of a previous study. 26 …”
Section: Discussionsupporting
confidence: 90%
“… 4 , 8 , 9 , 22–25 The mean total KPPS score in our study was 41.2±26.8, which was higher than the results of some previous studies. 14 , 15 , 22 According to the Ford classification, the most common types of PD-related pain are musculoskeletal pain and dystonia-related pain, followed by neuropathic radicular pain and central pain, which is consistent with the results of a previous study. 26 …”
Section: Discussionsupporting
confidence: 90%
“…In a study in Bulgaria, the Cronbach's alpha value obtained in 162 patients with idiopathic Parkinson's disease was 0.75 and in the stability analysis using the ICC, the value was 0.92, very similar to data found in the current study (ICC 0.99) (22) .…”
Section: Resultssupporting
confidence: 87%
“…The domains with lower pain scores were related to chronic pain, orofacial pain and radicular pain, similar to another KPPS scale validation study of the Bulgarian population, in which a relationship was also identified between domains of lower pain scores and chronic pain; discoloration, edema/swelling and orofacial pain. The most common type of pain is musculoskeletal, regardless of the instrument used to assess specific pain for PD ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Pain intensity, according to the KPPS – Swedish version, was a mean (standard deviation; SD) of 7.84 (12.8) out of a possible 168, which is lower than reported for the KPPS – Chinese version ( 24 ) with a mean (SD) score of 41.2 (26.8), KPPS – Bulgarian version ( 26 ) with a mean score of 21.1 (17.3), and the KPPS – Indian version ( 22 ) with a mean score of 16.02 (10.57). The period-prevalence (i.e.…”
Section: Discussionmentioning
confidence: 55%